2005
DOI: 10.1021/ja052337c
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Magnetic Resonance Detection of Cancer by Using Multifunctional Magnetic Nanocrystals

Abstract: The unique properties of magnetic nanocrystals provide them with high potential as key probes and vectors in the next generation of biomedical applications. Although superparamagnetic iron oxide nanocrystals have been extensively studied as excellent magnetic resonance imaging (MRI) probes for various cell trafficking, gene expression, and cancer diagnosis, further development of in vivo MRI applications has been very limited. Here, we describe in vivo diagnosis of cancer, utilizing a well-defined magnetic nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
502
0
11

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 826 publications
(518 citation statements)
references
References 27 publications
5
502
0
11
Order By: Relevance
“…The superparamagnetic Fe 3 O 4 nanocrystals shortened the water proton spin-spin relaxation times, by perturbing the magnetic relaxation processes of the protons in the surrounding water molecules resulting in a decrease in the MRI signal intensity and consequent darkening of the MR images [65] and [66]. Relaxivities were calculated using the relaxation times and the concentrations obtained from inductively coupled plasma atomic emission spectroscopy (ICP-AES) measurements with each type of nanoparticles.…”
Section: Relaxivitymentioning
confidence: 99%
“…The superparamagnetic Fe 3 O 4 nanocrystals shortened the water proton spin-spin relaxation times, by perturbing the magnetic relaxation processes of the protons in the surrounding water molecules resulting in a decrease in the MRI signal intensity and consequent darkening of the MR images [65] and [66]. Relaxivities were calculated using the relaxation times and the concentrations obtained from inductively coupled plasma atomic emission spectroscopy (ICP-AES) measurements with each type of nanoparticles.…”
Section: Relaxivitymentioning
confidence: 99%
“…[1][2][3][4] Targeted magnetic nanoparticles can be used to enhance the tissue contrast in magnetic resonance imaging (MRI), [5,6] to improve the efficiency in anticancer drug delivery, [7,8] and to eliminate tumor cells by magnetic fluid hyperthermia. [9][10][11] Recent synthetic progress makes it possible to produce mono disperse iron oxide nanoparticles with controlled sizes and magnetic properties, [12][13][14][15] but interactions between these nanoparticles and biomolecular entities, especially various tumor cells, are rarely studied owing to the challenge in nanoparticle functionalization and stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Recent synthetic progress makes it possible to produce mono disperse iron oxide nanoparticles with controlled sizes and magnetic properties, [12][13][14][15] but interactions between these nanoparticles and biomolecular entities, especially various tumor cells, are rarely studied owing to the challenge in nanoparticle functionalization and stabilization. [6,16] Herein we report a robust surface-functionalization approach to link monodisperse Fe 3 O 4 nanoparticles with nuclear localization signal (NLS) peptide and test their capability in targeting tumor-cell nuclei. In vitro experiments showed that the uptake of the NLS-labeled nanoparticles by HeLa cells is increased by up to 233% over the non-NLS-labeled nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…There is a great deal of interest in enhancing the utility of these tools in medicine and research through the development of molecularly-targeted MRI contrast agents. One example might be a chimeric molecule comprised of a contrast agent tethered to a molecule capable of binding to a specific protein or other biomolecular target with high affinity and specificity [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, we previously reported that a peptide selected from a phage display library to bind the yeast Gal80 protein can be linked to GdDOTA to create a reagent capable of imaging Gal80 protein in vitro [18,19].…”
Section: Introductionmentioning
confidence: 99%